2019
DOI: 10.4014/jmb.1809.09031
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Antimicrobial Peptide Allomyrinasin Derived from the Dynastid Beetle, Allomyrina dichotoma

Abstract: In a previous work, we performed de novo RNA sequencing of Allomyrina dichotoma using next generation sequencing and identified several antimicrobial peptide candidates based on transcriptome analysis. Among them, a cationic antimicrobial peptide, allomyrinasin, was selected bioinformatically based on its physicochemical properties. Here, we assessed the antimicrobial and anti-inflammatory activities of allomyrinasin against microorganisms and mouse macrophage Raw264.7 cells. Allomyrinasin showed antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Hepatic fibrosis and inflammation are important risk factor for the progression of NAFLD [19]. As ADLE showed anti-hepatofibrotic and anti-inflammatory activity [10,20], we checked whether ADLE can improve fibrosis and inflammation in the liver of HFD-fed mice. As shown in Figure 4A, hepatic steatosis demonstrating single large fat droplets in the cytoplasm of hepatocytes and ballooning of hepatocytes was clearly observed in the HFD-fed mice, but ADLE or Met treatment blocked the hepatic steatosis.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatic fibrosis and inflammation are important risk factor for the progression of NAFLD [19]. As ADLE showed anti-hepatofibrotic and anti-inflammatory activity [10,20], we checked whether ADLE can improve fibrosis and inflammation in the liver of HFD-fed mice. As shown in Figure 4A, hepatic steatosis demonstrating single large fat droplets in the cytoplasm of hepatocytes and ballooning of hepatocytes was clearly observed in the HFD-fed mice, but ADLE or Met treatment blocked the hepatic steatosis.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, only 305 of the 3070 HDP sequences deposited in the Antimicrobial Peptide Database (APD) are derived from insects ( Wang et al 2016 ). The HDP sequences and their biological activities have been described for several Coleoptera species, including: ( Allomyrina dichotoma ) ( Lee et al 2019 ), ( Octodonta nipae ) ( Meng et al 2019 ), Hylobius abietis ( Namara et al 2018 ), ( Nicrophorus vespilloides ) ( Vogel et al 2011 ), ( Tenebrio molitor ) ( Jacobs et al 2017 ), ( Calomera littoralis ) ( Rodríguez-García et al 2016 ), ( Protaetia brevitarsis seulensis ) ( Lee et al 2016 ), ( Tribolium castaneum ) ( Altincicek and Vilcinskas 2007 , Zou et al 2007 , Altincicek et al 2013 ), ( Holotrichia diomphalia ) ( Lee et al 1994 ), Zophobas atratus ( Bulet et al 1991 ), Allomyrina dichotoma ( Sagisaka et al 2001 ), ( Acalolepta luxuriosa ) ( Imamura et al 2009 ), and ( Sitophilus oryzae ) ( Login et al 2011 ). Our work further extends the list of HDP sequences to other species of Coleoptera.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the efficacy of certain types of AMPs in killing S. pseudintermedius and M. canis in vitro ( Santoro and Maddox, 2014 ; Simonetti et al, 2014 ); however, there are little data about the application of newly discovered AMPs to in vitro antimicrobial assays for clinical isolates of S. pseudintermedius and M. canis from China and their activity in a S. pseudintermedius -induced mouse skin infection model. Two short synthetic peptides, namely, allomyrinasin and andricin B, identified from Allomyrina dichotoma and Andrias davidianus , and three other original short-chain peptides have been previously described as effective against staphylococcal and fungal strains, which may serve as good candidates for further research ( Pei et al, 2018 ; Bao et al, 2019 ; Bessa et al, 2019 ; Chaparro-Aguirre et al, 2019 ; Lee et al, 2019 ). In our present study, we confirmed that allomyrinasin and andricin B exhibited potent antimicrobial activities by the disruption of microbial cell membrane.…”
Section: Introductionmentioning
confidence: 99%